The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40337-022-00529-6
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa risk and associated factors among Chilean nutrition students: a pilot study

Abstract: Background Orthorexia nervosa (ON) is characterized by an excessive, obsessive concern with healthy eating generating psychological complications and even malnutrition at a caloric and protein level. Current evidence suggests that people with greater food knowledge are the most likely to be affected, placing nutrition students as a populational risk group. Since there are no nationwide studies dealing with orthorexia nervosa in this risk group, the present pilot study intends to identify risk f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
0
13
1
2
Order By: Relevance
“…Otherwise, the non-presence in social networks can generate anxiety. (64) Likewise, the above may be associated with anxiety disorders and depression, (65,66) eating disorders, (67) selfregulation, and social skills problems in life offline. (68) A second factor was the fear of missing something great (FMS).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the non-presence in social networks can generate anxiety. (64) Likewise, the above may be associated with anxiety disorders and depression, (65,66) eating disorders, (67) selfregulation, and social skills problems in life offline. (68) A second factor was the fear of missing something great (FMS).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral rigidity is a characteristic of individuals who tend to follow rules more than others. Considering that one of the characteristics of orthorexia nervosa is the tendency to present an excessive preoccupation with food and the non-acceptance of a different diet [ 35 , 36 ], which involves being under the control of strict rules regarding one’s own food, it is likely that behavioral rigidity interferes with the food patterns adopted by people and is also a feature of orthorexia nervosa. Thus, based on the finding that women are more likely to present orthorexic self-reports, it seems logical that behavioral rigidity is associated with being female, which points to the need for interventions aimed at producing behavioral flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…HO can be the successful result of dissemination campaigns aimed to increase nutrition knowledge from WHO and National recommendations, but the proposed etiology of ON includes high level of education, pseudoscientific nutritional news on social media and psychological factors[ 12 ]. From a study carried out in nutrition and dietetics, university students emerged that Instagram use might be considered as an ON-risk factor[ 47 ]. Besides, K10 median of the scores of students enrolled in health-related study courses was higher than those of non-health-related degree courses[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a generalization to the whole population should not be made, considering the recent suggestions on the need for further investigation of the comorbidity between ON and OCD across different cultural groups[ 50 ], it emerged that ON could be an indicator/symptom of other problems related to body image perception, as well as high PA, psychological distress, appearance, fitness, health, or IO, in some university students. Accordingly, recent studies have found relationships between ON, vigorous-intensity PA and dieting[ 47 , 57 ]. In our study, the ORTO-7 was found to be independent from these confounders, after the exclusion of UW, OW, OB, and EAT-26 and K10 positive students, suggesting the possibility of defining subjects with ON.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation